Phenotypic and Transcriptomic Lymphocytes Changes in Allograft Recipients After Intravenous Immunoglobulin Therapy in Kidney Transplant Recipients - Pilon, Caroline; Bigot, Jeremy; Grondin, Cynthia; Thiolat, Allan; Lang, Philippe; Cohen, José L.; Grimbert, Philippe; Matignon, Marie (Frontiers in Immunology, 2020)
High dose intravenous immunoglobulin (IVIG) are widely used after kidney transplantation and its biological effect on T and B cell phenotype in the context of maintenance immunosuppression was not documented yet. We designed a monocentric prospective cohort study of kidney allograft recipients with anti-HLA donor specific antibodies (DSA) without acute rejection on screening biopsies treated with prophylactic high-dose IVIG (2 g/kg) monthly for two months. Any previous treatment with Rituximab was an exclusion criterion. We performed an extensive analysis of phenotypic and transcriptomic T and B lymphocytes changes and serum cytokines after treatment (day 60). Twelve kidney transplant recipients who completed at least two courses of high-dose IVIG (2 g/kg) were included in a median time of 45 (12-132) months after transplant. Anti-HLA DSA characteristics were similar before and after treatment. At D60, PBMC population distribution was similar to the day before the first infusion. CD8+ CD45RA+ T cells and naïve B-cells (Bm2+) decreased (P=0.03 and P=0.012 respectively) whereas Bm1 (mature B-cells) increased (P=0.004). RORt serum mRNA transcription factor and CD3 serum mRNA increased 60 days after IVIG (P=0.02 for both). Among the 25 cytokines tested, only IL-18 serum concentration significantly decreased at D60 (P=0.03). In conclusion, high dose IVIG induced limited B cell and T cell phenotype modifications that could lead to anti-HLA DSA decrease. However, no clinical effect has been isolated and the real benefit of prophylactic use of IVIG after kidney transplantation merits to be questioned.